Preliminary binary ethylenimine (BEI) inactivated bovine papillomavirus (BPV) vaccine trial against cutaneous warts in bull calves: a pathological assessment - Pangty, Kanchan; Singh, Shweta; Pandey, Awadh B.; Somvanshi, Ramesh (Brazilian Journal of Veterinary Pathology, 2010)
A preliminary prophylactic and therapeutic vaccine trial was successfully conducted in bull calves with binary ethylenimine (BEI) inactivated saponized crude cutaneous warts bovine papillomavirus 1 and 2 (CW BPV-1 & -2) vaccine. In Prophylactic Group of vaccinated animals no temperature, untoward reaction or nodule formation was seen at vaccine inoculation site. After challenge with BPV inoculum, cutaneous warts (CWs) failed to develop in this group indicating that vaccine was effective. In Therapeutic Group, before vaccination in two animals CWs were experimentally induced. In one animal, luxuriant cauliflower-like and in other linear slow growth was observed. After vaccination, CWs in both animals became dried and growth was arrested. It appeared that tumours were regressing which was confirmed by further clinical observations as very little tumour-scar was left at termination of experiment. Histopathologically, both cases were diagnosed as regressing occult/ early fibroblastic type papilloma. Mononuclear cellular infiltration/ aggregates around hair follicles and in tumour stroma were noted. As compared to first case (cauliflower- like/ fast growing) in second case (linear growth/ fast regressing), in addition to other findings mononuclear cellular inflammatory reaction were more pronounced. The clinical regression results are in accordance with histopathological findings of degree of infiltration of lymphocytes and this trial showed that both type use of BEI inactivated saponized crude CW BPV-1&-2 vaccine gave encouraging results with fast regression/ prevention of CWs.